Maximum Profit Optimization of The Walang Marthafons Smoked Fish Business in Poka Village, Ambon - Eygner Talakua; Angela Ruban; Janer Sangaji (Universitas Islam Lamongan, 2026)
The main constraint faced by the Walang Marthafons smoked fish business in Poka Village is the inefficient use of production factors, resulting in suboptimal profits and a moderate value-added ratio. This study aims to analyze profit maximization using a linear programming approach. A case study method with a quantitative approach was applied. Data were collected through interviews and direct observations of the business owner. The analysis consisted of two stages: (1) profit analysis to determine actual profit based on total revenue and production costs, and (2) linear programming to identify the optimal production combination under constraints of raw materials, labor, and production capacity. The results indicate that the actual profit per production period is Rp 983.702, while the maximum attainable profit is Rp 1.490.430, representing an increase of 51,5%. The optimal production level is 38.8 kg per period, consisting of 22,5 kg of trevally, 5,8 kg of barramundi, and 10,5 kg of grouper. These findings suggest that production optimization can significantly improve business performance. Business owners are encouraged to adopt optimization techniques, while policymakers should support small-scale fisheries through training and improved access to resources, technology, and financing.